Engineering Chimeric Antigen Receptor T Cells against Immune Checkpoint Inhibitors PD-1/PD-L1 for Treating Pancreatic Cancer - Ching-Yao Yang; Ming Huei Fan; Carol H. Miao; Yi Jen Liao; Ray-Hwang Yuan; Chao Lien Liu (Molecular Therapy: Oncolytics, 2020)
Pancreatic ductal adenocarcinoma (PDAC) is an aggressive disease with a 5-year survival rate of 9%. Major obstacles to successful treatment of pancreatic cancer are the immunosuppressive tumor microenvironment (TME) and antigenic complexity or heterogeneity. Programmed death-ligand 1 (PD-L1) is expressed on PDAC and immunosuppressed cells within the TME, providing suitable immunotherapy targets. We applied a chimeric antigen receptor (CAR) strategy to target immune checkpoint programmed death-1 (PD-1)/PD-L1 interactions. Lentiviral vectors were used to express the extracellular domain of human PD-1 (PD-1-CD28-4-1BB activating chimeric receptor [PD1ACR]) or the single-chain variable fragment (scFv) region of anti-PD-L1 (PDL1CAR) that binds to PD-L1, and each was fused to intracellular signaling domains containing CD3 zeta, CD28, and 4-1BB (CD137). Both engineered CAR T cells recognized and eliminated PD-L1-overexpressing CFPAC1 cells efficiently at approximately 80% in vitro. Adoptive transfer of both CAR T cells enhanced T cell persistence and induced specific regression of established CFPAC1 cancer by >80% in both xenograft and orthotopic models. Ki67 expression in tumors decreased, whereas proinflammatory cytokines/chemokines increased in CAR T cell-treated mouse sera. PD1ACR and PDL1CAR obtained a similar therapeutic efficacy. Thus, these armed third-generation PD-L1-targeted CAR T cells confer antitumor activity and the ability to combat T cell exhaustion, providing a potentially new and innovative CAR T cell immunotherapy against pancreatic cancers.